Collaborative teams that transform schools : the next step in PLCs - Marzano, Robert J. (Marzano Resources, 2016)
Discover a practical, comprehensive model of effective professional learning communities. In this user-friendly guide, educators explore research-based steps and strategies designed to increase the effectiveness of collaborative teams and enhance PLCs. Examine how the PLC process can transform critical components of education-including curriculum, assessment, instruction, and teacher development-and use reproducible agendas, scales, and checklists to improve schoolwide practices.